Photodiodes based in La0.7Sr0.3MnO3/single layer MoS2 hybrid vertical heterostructures. (21st July 2017) - Niu, Yue; Frisenda, Riccardo; Svatek, Simon A; Orfila, Gloria; Gallego, Fernando; Gant, Patricia; Agraït, Nicolás; Leon, Carlos; Rivera-Calzada, Alberto; De Lara, David Pérez; Santamaria, Jacobo; Castellanos-Gomez, Andres
Abstract: The fabrication of artificial materials by stacking of individual two-dimensional (2D) materials is amongst one of the most promising research avenues in the field of 2D materials. Moreover, this strategy to fabricate new man-made materials can be further extended by fabricating hybrid stacks between 2D materials and other functional materials with different dimensionality making the potential number of combinations almost infinite. Among all these possible combinations, mixing 2D materials with transition metal oxides can result especially useful because of the large amount of interesting physical phenomena displayed separately by these two material families. We present a hybrid device based on the stacking of a single layer MoS2 onto a lanthanum strontium manganite (La0.7 Sr0.3 MnO3 ) thin film, creating an atomically thin device. It shows a rectifying electrical transport with a ratio of 10 3, and a photovoltaic effect with V oc up to 0.4 V. The photodiode behaviour arises as a consequence of the different doping character of these two materials. This result paves the way towards combining the efforts of these two large materials science communities.